2011
DOI: 10.1016/j.jtcvs.2011.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pulmonary hypertension on outcomes after aortic valve replacement for aortic valve stenosis

Abstract: Objective The presence of pulmonary hypertension (PH) historically has been considered a significant risk factor affecting early and late outcomes following valve replacement. Given the number of recent advances in the management of PH following cardiac surgery a better understanding of the impact of PH on outcomes may assist in the clinical management of these patients. The purpose of this study was to determine if pulmonary hypertension remains a risk factor in the modern era for adverse outcomes following a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(147 citation statements)
references
References 19 publications
(17 reference statements)
3
129
1
6
Order By: Relevance
“…Likewise, Tamburino et al, 11 in 663 consecutive patients who underwent TAVI with the CoreValve device, did not identify severe PH as an independent predictor of 30-day mortality. In contrast, PH has early clinical implications after surgical AVR: Melby et al, 24 in 1080 patients who underwent AVR for primary aortic valve stenosis, found significantly higher 30-day mortality in patients with PH (9.3% versus 5.4%; P=0.18). Severe PH was also an independent predictor of early mortality in the study of Di Eusanio et al 25 of 2256 patients managed by AVR (odds ratio, 5; 95% CI, 1.1-5.9).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Tamburino et al, 11 in 663 consecutive patients who underwent TAVI with the CoreValve device, did not identify severe PH as an independent predictor of 30-day mortality. In contrast, PH has early clinical implications after surgical AVR: Melby et al, 24 in 1080 patients who underwent AVR for primary aortic valve stenosis, found significantly higher 30-day mortality in patients with PH (9.3% versus 5.4%; P=0.18). Severe PH was also an independent predictor of early mortality in the study of Di Eusanio et al 25 of 2256 patients managed by AVR (odds ratio, 5; 95% CI, 1.1-5.9).…”
Section: Discussionmentioning
confidence: 99%
“…55 The presence of PH at rest or during exercise should therefore be included in perioperative risk assessment of mitral and aortic valve replacement. 56,57 In older patients with severe mitral valve stenosis and PH, the perioperative mortality increases to 20%; therefore, the indication of valve surgery has to be proven carefully. 56 Preoperative PH was also an independent risk factor for long-term survival in patients with aortic valve replacement.…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…56 Preoperative PH was also an independent risk factor for long-term survival in patients with aortic valve replacement. 57,58 Patients with valvular disease and normal or mildly elevated PASP at rest may develop severe PH during exercise, which may be unrelated to the resting pressure. 37,59 The level of increase in PASP depends on the ability to successfully recruit the pulmonary vasculature to accommodate increased blood flow with exercise, the contribution (or proportion) of the reduction in cross-sectional area of the pulmonary circulation, the reduction in pulmonary vascular compliance, and the increase in LAP, each of which may be abnormal at rest.…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…PH is a common complication of mitral valve disease and may affect as many as 73% of patients depending on disease severity [32,33]. The prevalence of PH in patients with aortic stenosis is lower than in those with mitral stenosis but is still considerable at ,30-50% [34][35][36].…”
Section: Epidemiology and Natural History Of Ph-lhdmentioning
confidence: 99%